North Atlantic control on precipitation pattern in the eastern Mediterranean/Black Sea region during the last glacial - Kwiecien, Olga; Arz, Helge Wolfgang; Lamy, Frank (Quaternary research, 2009)
Based on proxy records from western Black Sea cores, we provide a comprehensive study of climate change during the last glacial maximum and late-glacial period in the Black Sea region. For the first time we present a record of relative changes in precipitation for NW Anatolia based on variations in the terrigenous supply expressed as detrital carbonate concentration. The good correspondence between reconstructed rainfall intensity in NW Anatolia and past western Mediterranean sea surface temperatures (SSTs) implies that during the glacial period the precipitation variability was controlled, like today, by Mediterranean cyclonic disturbances. Periods of reduced precipitation correlate well with low SSTs in the Mediterranean related to Heinrich events H1 and H2. Stable oxygen isotopes and lithological and mineralogical data point to a significant modification in the dominant freshwater/sediment source concomitant to the meltwater inflow after 16.4 cal ka BP. This change implies intensification of the northern sediment source and, with other records from the Mediterranean region, consistently suggests a reorganization of the atmospheric circulation pattern affecting the hydrology of the European continent. The early deglacial northward retreat of both atmospheric and oceanic polar fronts was responsible for the warming in the Mediterranean region, leading simultaneously to more humid conditions in central and northern Europe.